Analysis of cascaded multilevel inverters for active harmonic filtering in distribution networks. (March 2015) - Panda, Anup Kumar; Patnaik, Sushree Sangita
Highlights: Realization of shunt active power filter for three-phase three-wire power systems. Development of cascaded multilevel inverters and their implementation on APFs. Implementation of bacterial foraging optimization for dc-link voltage regulation. Real-time analysis under various supplies with Opal-RT real-time simulator. Comparison of 3, 5, 7 and 9 level inverters in current harmonic compensation. Abstract: This paper aims at the investigation of an active power filter (APF) comprised of a transformerless multilevel inverter (MLI) for power conditioning in three-phase three-wire distribution network. The inverter topologies used here are three, five, seven and nine-level. The system configuration mainly involves cascaded MLI structure of APF, generation of compensation filter currents based on instantaneous active and reactive current component ( id – iq ) method and dc-link voltage regulation using a PI controller. Not many papers focus on the regulation of dc-link capacitor voltage. Here we have proposed the implementation of bacterial foraging optimization (BFO) to extract the gains of PI controller. The proposed work provides improved dc-link voltage regulation, quick prevail over current harmonics and reduction of overall source current THD. Adequate MATLAB/Simulink simulation results are presented for the different cascaded MLIs discussed above. Additionally, the performance has been validated in real-time using Opal-RT Lab simulator considering three different conditions of supply i.e., balanced sinusoidal, balanced non-sinusoidal and unbalanced sinusoidal.